The pragmatics of adaptability - Silva, Daniel N.; Mey, Jacob (Pragmatics & beyond ;, 2021)
"Humans are adaptive beings. Gradually, we have produced the fundamental capacities for our cooperation, recognition of intentions, and interaction which led to the development of language and culture. The present collective volume builds on an orientation to pragmatics as the sustained and principled human adaptability in interaction, form, and meaning. Working on different strands of such a socially oriented pragmatics, the authors gathered in this volume study the adaptability of language as shaped by the conditions of society, culture, and cognition. Grouped in four sections, the book's chapters explore the embedding of adaptability in language ideology, text, communicative practice, and learning. Adopting these various perspectives, the authors gauge how language users navigate the different layers of societal, cognitive, and communicative constraints, while adapting their communicative practices, language ideologies, and technologies of interaction to their everyday living conditions"--